MP3 : the definitive guide - Hacker, Scot (O'Reilly, 2000)
"MP3 is the most popular compressed file format for easy digital distribution of sound and music over the Internet. MP3: The Definitive Guide is the bible of this phenomenon. It's a guide to the juicy bits for MP3 power users. Ripping and encoding are covered in depth, from a true audiophile's perspective. You'll learn exactly what it means to listen to a perceptual codec and how it affects the way you should record, make tests, and listen to your MP3 files. You'll find a detailed examination of the codec itself and its development, as well as how MP3 files compare with other common compression formats." "Like MP3, The Definitive Guide doesn't limit itself to one operating system or even one player. It contains advanced information for using MP3 files on all the most popular operating systems, including Windows, Linux, Macintosh, and BeOS. You'll find plenty of information about WinAmp, but players on other platforms are also covered in depth. You'll also find an expert's guide to MP3 files online, web sites to look for, ways to work with newsreaders and ftp, and the latest word on the rapidly evolving technologies of the MP3 audio revolution."--Jacket.